MicroRNA-binding site polymorphisms and risk of colorectal cancer: A systematic review and meta-analysis - Gholami, Morteza; Larijani, Bagher; Sharifi, Farshad; Hasani-Ranjbar, Shirin; Taslimi, Reza; Bastami, Milad; Atlasi, Rasha; Amoli, Mahsa M (Cancer medicine, 2019)
Genetic variations in miRNAs binding site might participate in cancer risk. This study aimed to systematically review the association between miRNA-binding site polymorphisms and colorectal cancer (CRC). Electronic literature search was carried out on PubMed, Web of Science (WOS), Scopus, and Embase. All types of observational studies till 30 November 2018 were included. Overall 85 studies (21 SNPs) from two systematic searches were included analysis. The results showed that in the Middle East population, the minor allele of rs731236 was associated with decreased risk of CRC (heterozygote model: 0.76 [0.61-0.95]). The minor allele of rs3025039 was related to increased risk of CRC in East Asian population (allelic model: 1.25 [1.01-1.54]). Results for rs3212986 were significant in overall and subgroup analysis (P < .05). For rs1801157 in subgroup analysis the association was significant in Asian populations (including allelic model: 2.28 [1.11-4.69]). For rs712, subgroup analysis revealed a significant (allelic model: 1.41 [1.23-1.61]) and borderline (allelic model: 0.92 [0.84-1.00]) association in Chinese and Czech populations, respectively. The minor allele of rs17281995 increased risk of CRC in different genetic models (P < .05). Finally, rs5275, rs4648298, and rs61764370 did not show significant associations. In conclusion, minor allele of rs3025039, rs3212986, and rs712 polymorphisms increases the risk of CRC in the East Asian population, and heterozygote model of rs731236 polymorphism shows protective effect in the Middle East population. In Europeans, the minor allele of rs17281995 may increase the risk of CRC, while rs712 may have a protective effect. Further analysis based on population stratifications should be considered in future studies.
Keywords: Gene Expression Regulation, Neoplastic; MicroRNAs; microRNAs; kolorektální nádory; Genetic Predisposition to Disease; vazebná místa; Risk Factors; Dálný východ; Česká republika; mikro RNA; regulace genové exprese u nádorů; 3' nepřekládaná oblast; jednonukleotidový polymorfismus; Czech Republic; Binding Sites; Asia, Eastern; Střední východ; Polymorphism, Single Nucleotide; lidé; Humans; rizikové faktory; pozorovací studie jako téma; Observational Studies as Topic; 3' Untranslated Regions; meta-analysis; Colorectal Neoplasms; colorectal cancer; Alleles; Asian People; Asijci; alely; genetická predispozice k nemoci; Middle East; polymorphism